(untitled) (Fiep Bulletin - online, 2015)
The objective of this study is to describe IDCM, using anthropometric and coordinative variables. Having 55 female children participated of the study with age among 6 and 11 years, apprentices of artistic gymnastics on a sporting center of the city of Rio de Janeiro. Descriptive research. In the sample the index of modified corporal development was evaluated Siret (1991) and for the verification of the coordinative variable the test was used Burpee. The accelerated maturational moment is usually marked by larger stature and corporal mass, however this increase was not found in the result of the coordination test. We recommend studies about the relationship between IDCM and physical qualities in several individual and collective modalities.